It's all about balancing-handling free speech issues under the German Basic Law - Dieter Dörr; Alexander Natt (Forensic Science Today - Peertechz Publications, 2020)
The first Articles of the German basic law contain the so-called basic rights. As Art. 1 para. 3 states they bind the legislature, the executive and the judiciary and therefore all state authority as directly applicable law. At first glance this sounds familiar and very similar to the bill of rights respectively the first ten amendments to the United States Constitution. But a closer look reveals that the German approach-especially handling free speech issues- is in many ways different from the situation in the United States [1].